2021
DOI: 10.20944/preprints202112.0151.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Some Properties of the Basins of Attraction of the Newton’s Method for Simple Nonlinear Geodetic Systems

Abstract: The research presented in this paper concerns the determination of the attraction basins of the Newton’s iterative method which was used to solve the non-linear systems of observational equations associated with the geodetic measurements. The authors considered simple observation systems corresponding to the intersections, or linear and angular resections, used in practice. The main goal was to investigate the properties of the sets of convergent in the initial points of the applied iterative method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Research about this topic can be found in references [24,25]. In recent years, dynamic studies have been carried out to analyze the stability of iterative methods [26][27][28].…”
Section: Stability Analysismentioning
confidence: 99%
“…Research about this topic can be found in references [24,25]. In recent years, dynamic studies have been carried out to analyze the stability of iterative methods [26][27][28].…”
Section: Stability Analysismentioning
confidence: 99%